Peran kepuasan kerja dalam memediasi hubungan antara stres kerja dan beban kerja terhadap kinerja - Aulia, Khisma Nur; Setiani, Setiani (Nur Science Institute, 2024)
This research aims to find out how members of the Malang City Police Traffic Unit perform regarding work stress and workload, with job satisfaction as a mediating factor. The population of this research is all members of the Malang City Police Traffic Unit, with a sample of 136 personnel, whose data was obtained from a questionnaire with Structural Equation Model (SEM) analysis based on Partial Least Square (PLS). Research findings show that performance is significantly negatively influenced by work stress and workload. The relationship between performance and job satisfaction is significantly positive. However, job satisfaction does not influence members' work performance or stress. However, the relationship between workload and performance can be mediated by job satisfaction. These findings can be used as the basis for increasing job satisfaction and reducing work stress for Malang City Police Traffic Unit personnel.